Sliding window soft-SCL decoders for asynchronous polar-coded modulation - Hu, Yaoyue (2023)
Asynchronous polar-coded modulation (A-PCM) outperforms multilevel polar-coded modulation by taking advantage of spatial coupling among several coded blocks. To further improve the performance of A-PCM, a cyclic-redundancy-check (CRC) aided sliding window soft successive cancellation list (CA-SWSCL) decoder is proposed to exploit the benefits of spatial coupling and CRC-aided iterative message passing. This approach includes both soft-output and hard-output iteration processes, where the CRC results are not only used for early termination but also served as an execution flag of the hard-output iteration process. In the case of rate half polar-coded modulation with frame length 128, A-PCM with the proposed CA-SWSCL achieves the best block-error-rate (BLER) performance among the state-of-art polar-coded modulation schemes.